The concept of fashionable clothing and brands according to selected young professionals - Siapno, Jessica Rae D.
Foreign brands have been succeeding in the global fast fashion race, leaving local brands under the shadow of their success. As a result, foreign brands have slowly become the benchmark for fashionable clothing and brands of Filipino consumers. This study aimed to describe the concept of fashionable clothing and brands of Filipino consumers, specifically that of young professionals. In this descriptive and qualitative study, 60 survey respondents and nine focus group discussion participants identified retail brands they consider fashionable, key words they associate with fashionable clothing, and related their concept of fashionable clothing to George Sproles" (1974) three life style functions. Purposive and snowball sampling were used to select the respondents of the study. The results of the study reveal that the selected Filipino consumer group of young professionals consider foreign brands as more fashionable than local brands. Secondly, the words they associate with fashionable clothing such as comfort, style, quality, versatility, fit and affordability are directly related to their current clothing needs as young professionals. Finally, their concept of fashionable clothing is influenced by sex appeal and social role performance, but not prestige position. Further studies on the feasible application of the foreign fast fashion formula to local brands, a psychological analysis of the responses, and the exploration of new consumer groups and mix of local and foreign brands to be applied in the existing study are recommended.